2020
DOI: 10.1007/s40264-020-00952-1
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir in Treatment of COVID-19: A Systematic Benefit–Risk Assessment

Abstract: Introduction There is a need to identify effective, safe treatments for COVID-19 (coronavirus disease) rapidly, given the current, ongoing pandemic. A systematic benefit-risk assessment was designed and conducted to examine the benefit-risk profile of remdesivir in COVID-19 patients compared with standard of care, placebo or other treatments. A key objective of this study was to provide a platform for a dynamic systematic benefit-risk evaluation, which starts with inevitably limited information (to meet the ur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…A large number of suggested treatments such as ivermectin, hydroxychloroquine, and azithromycin are currently under investigation. Among them, hydroxychloroquine, azithromycin, and recently remdesivir showed acceptable results in clinical trials, as of June 2020 [4][5][6][7][8][9][10]. Nevertheless, the results of these interventions are not completely satisfactory and studies for other medications are still warranted .…”
Section: Covid-19mentioning
confidence: 99%
“…A large number of suggested treatments such as ivermectin, hydroxychloroquine, and azithromycin are currently under investigation. Among them, hydroxychloroquine, azithromycin, and recently remdesivir showed acceptable results in clinical trials, as of June 2020 [4][5][6][7][8][9][10]. Nevertheless, the results of these interventions are not completely satisfactory and studies for other medications are still warranted .…”
Section: Covid-19mentioning
confidence: 99%
“…Recently, Yeming et al published the results of the NCT04257656 clinical trial, which showed no clear outcome because of the death or discharge of patients ( 73 ). Moreover, in another clinical trial, the benefit in terms of the time to clinical improvement was not statistically significant (21 vs. 23 days), even though the study was underpowered ( 74 ). There are limited safety data for remdesivir, which should be obtained in further studies.…”
Section: Potential Therapeutic Approachesmentioning
confidence: 90%
“…Based on the current pandemic, a report has recently been demonstrated an adaptive, randomized, placebo-controlled, double blind phase 3 (NCT04257656) clinical trial to evaluate the efficacy and safety of this drug (200 mg on day 1 and 100 mg once daily for 9 days) combined with the supportive care in the hospitalized 237 COVID-19 patients (Scavone et al, 2020;Wang et al, 2020b). But this initial studies with remdesivir showed no benefit as underpowered (Davies et al, 2020;Wang et al, 2020a), this changed with the NIH study called COVID-19 Adaptive Treatment Trial (ACTT 3) in which the safety and efficacy of a treatment regimen consisting of remdesivir plus the interferon beta-1a immunomodulator in patients with coronavirus 2019 (COVID-19) will be evaluated (National Institutes of Health, 2020). Remdesivir has recently been granted a conditional marketing authorization in the European Union countries by the European Commission (Agency, 2020).…”
Section: Baloxavir Marboxil (S-033188)mentioning
confidence: 99%
“…But this initial studies with remdesivir showed no benefit as underpowered ( Davies et al., 2020 ; Wang et al., 2020a ), this changed with the NIH study called COVID-19 Adaptive Treatment Trial (ACTT 3) in which the safety and efficacy of a treatment regimen consisting of remdesivir plus the interferon beta-1a immunomodulator in patients with coronavirus 2019 (COVID-19) will be evaluated ( National Institutes of Health, 2020 ). Remdesivir has recently been granted a conditional marketing authorization in the European Union countries by the European Commission ( Agency, 2020 ).…”
Section: Old and New Drugs Potentially Purposed For Covid-19 Treatmenmentioning
confidence: 99%